Promoting sleep health in future healthcare professionals: development and validation of a multi-component lifestyle intervention module for nursing students - Wang, Jing; Ishak, Ismarulyusda; Mazri, Fatin Hanani; Siau, Ching Sin; Xin, Fengxue; Mat Ludin, Arimi Fitri (Frontiers in Public Health, 2025)
BackgroundSleep disturbances are a widespread public health concern among nursing and healthcare students globally, with consequences for academic performance, mental health, and long-term professional competence. Despite evidence linking multiple lifestyle factors, such as physical activity, diet, stress management, and relaxation techniques, to sleep quality, comprehensive interventions integrating these elements remain limited in nursing education. We plan to conduct a pre-registered 4-week pre–post effectiveness pilot and will report effect sizes (Cohen’s d, 95% CI).MethodsThis study applied the Sidek Module Development Model (SMDM) to design and validate a multi-component lifestyle intervention module aimed at improving sleep quality among vocational nursing students in China. The module integrated five evidence-based components: physical activity, psychoeducation, music therapy, meditation, and nutrition. Content validity and educational quality were assessed by six independent experts using the Content Validity Index (CVI) and the Template for Evaluating Patient Education Documents (TEMPtED). Reliability and acceptability were further evaluated among 47 nursing students through a Likert-scale questionnaire, with Cronbach’s alpha computed for internal consistency.ResultsThe module demonstrated strong psychometric properties. The overall scale-level content validity index (S-CVI/Ave) was 0.985, exceeding the recommended threshold and confirming excellent content validity. All five sub-modules were rated as “Excellent” in educational quality based on the TEMPtED evaluation. Student feedback yielded a Cronbach’s alpha of 0.980, reflecting high internal consistency and suggesting that the module’s structure and materials were coherent and well-received. These results indicate strong preliminary evidence supporting the module’s validity and reliability during the development and validation phase.ConclusionThis study developed and validated a scientifically robust, educationally feasible, and culturally responsive lifestyle module designed to promote sleep health among nursing students. While the findings demonstrate strong content validity, educational quality, and internal consistency, they represent an initial validation stage rather than evidence of intervention effectiveness. The validated framework provides a solid foundation for future implementation, cross-cultural adaptation, and evaluation studies aimed at examining its impact and long-term sustainability across diverse educational contexts.